DESIGNING ACCOUNTING SYSTEM AT UD.TANG - Friendty Friendty; Anita Anita (ConCEPt - Conference on Community Engagement Project, 2022)
Tang is a micro, small and medium enterprise that sells sago flour and tapioca flour. Recording transactions at UD. Tang is still done manually, recorded in the book owned by the business owner so the owner will find it challenging to know the profit or loss and the development of the business, especially in financial terms. This community service activity aims to establish a system that can produce financial reports that help the owner develop their businesses. The data collection method used in this community service activity is by conducting interviews, observation, and documentation. The result of this community service activity is forms and reports that will help the owner record transactions and produce accurate financial reports. After implementing the system, the business owner does not need to record transactions manually anymore and can find out the condition of the company by viewing reports that the system can generate.